Development of Safety Plan Building Based on Work Breakdown Structure (WBS) in Campus Area of UI Depok to Reduce Work Accident - Astrid Dwi Lestari; Ayu Herzanita; Yusuf Latief (Journal of International Conference Proceedings (JICP), 2021)
There is very little discussion about the needs of occupational health within the University area. In fact, the University is a place where interaction occurs not only for lecturers and students, but also employees, contractors and other visitors with very varied backgrounds and cultures. The lack of application of OHSMS in the construction sector in the University area causes a high number of work accidents. Making a safety plan at the initiation stage can reduce and prevent potential hazards that will occur. One of the methods can be used to reduce work accidents is by developing a safety plan using WBS (Work Breakdown Structure). This study aims to develop a WBS-based construction occupational safety and health plan for structural and architectural work buildings. This study develops a safety plan based on Regulation of Minister of PUPR No. 21 of 2019. This study uses literature study techniques for risk identification and questionnaires validation by experts with a minimum of 5 years experiences in OHS construction project. The result of this study is identification of hazards, impacts, prevention, OHS objective and programs. The results will be used for the development of a safety plan, intending to improve occupational safety and health performance and reduce occupational accidents in construction projects.